Effect of Probiotic Streptococcus salivarius K12 and M18 Lozenges on the Cariogram Parameters of Patients With High Caries Risk: A Randomised Control Trial - Poorni, Saravanan; Nivedhitha, MS; Srinivasan, Manali; Balasubramaniam, Arthi (Curēus (Palo Alto, CA), 2022)
To evaluate the effect of Probiotic K12 and M18 Lozenges on the Cariogram (Cariogram Mobile application Version 1.3 developed by Wong Jung Ming, Faculty of Dentistry, National University of Singapore) parameters of patients with high caries risk. Fourty-two subjects were randomly allocated to Group 1 and 2 who received BLIS K12 and BLIS M18 probiotics (Blis Probiotics, Dunedin, New Zealand) respectively along with oral hygiene instructions and Group 3 (control) received only oral hygiene instructions with 1:1:1 allocation ratio. Subjects were instructed to follow the instructions and use the probiotics for a period of three months. Their caries risk was assessed using Cariogram software at baseline and 30 days after the use of probiotics. Change in the chance to avoid new cavities was recorded and statistically analysed using appropriate statistical tests. About 38 subjects completed the trial with a drop-out count of eight. Multiple imputations were carried out for the missing data using an expectation-maximization algorithm. The mean percentage of actual chance to avoid new cavities was found to be 47.14 ± 6.837; 41.36 ± 16.04 and 32.50 ± 14.54 among the subjects in Group 1, Group 2, and Group 3 respectively. The mean percentage difference between the three groups was found to be statistically significant (p-value = 0.047). Dunn's pair-wise comparison showed a significant mean percentage difference between Group 1 (BLIS K12) and Group 3 (control) (p=0.020). It can be concluded that the use of BLIS K12 and BLIS M18 probiotics for three months resulted in a considerable decrease in the caries risk. Further long-term clinical trials are needed to evaluate the difference in caries risk following the use of BLIS K12 and BLIS M18 among different age and risk groups.